An ethnobotanical survey of medicinal plants of Yazikonak and Yurtbasi districts of Elazig province, Turkey - Cakilcioglu, U.; Sengun, M. T.; Turkoglu, I. (Academic Journals, 2010)
This study, conducted between 2008 - 2009, analyzed the medicinal plant species traditionally used in Yazikonak and Yurtbasi districts of Elazig province, Turkey and the local names of these plants. Within the scope of the study, the plant species were collected; herbarium materials were prepared; and the specimens were nomenclatured. A total of 41 medical plants belonging to 17 families were identified in the region. The most common medicinal plant families were Asteraceae (>29% of use - reports), Rosaceae (>15%), Lamiaceae (>12%); the most common preparations were infusion and decoction. The plant species Thymus haussknechtii Velen, Anthemis wiedemanniana Fisch. and Mey. are endemic to the study area, and are used for treating various diseases. Since they are also used in other parts of the world for treating similar diseases, they can be considered as pharmacologically effective. This type of ethno-botanic study enables proper transfer of knowledge of plant - based treatments (our natural inheritance) to future generations.
Keywords: Ethnobotany; medicinal plants; Endemic; Yazikonak; Yurtbasi (Elazig-Turkey)